2017
DOI: 10.1155/2017/5491838
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Hypertension: A Cross-Sectional Study in Urban Varanasi

Abstract: Hypertension is a major public health problem and important area of research due to its high prevalence and being major risk factor for cardiovascular diseases and other complications. Objectives. (1) To assess the prevalence of hypertension and its associated factors and (2) to estimate awareness, treatment, and adequacy of control of hypertension among study subjects. Methods and Materials. A community based cross-sectional study with multistage sampling design was conducted among urban population of Varanas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

69
288
10
34

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(401 citation statements)
references
References 28 publications
(54 reference statements)
69
288
10
34
Order By: Relevance
“…Among them 81% of hypertensive were already diagnosed to have HTN while 19% were newly detected hypertensive according to JNC VIII criteria. The overall prevalence of hypertension in the present study (30.5%) was lower compared to study conducted in Raichur by Chethana et al 2,4,6 The prevalence was higher in comparison with the prevalence reported in study conducted by Bhardwaj et al in Nagpur as well as studies done by Mohan in Chennai and By Kaur et al in South India. [7][8][9] Female exhibit higher prevalence of hypertension than their male counterparts (F: 53.6% and M: 46.4%).…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Among them 81% of hypertensive were already diagnosed to have HTN while 19% were newly detected hypertensive according to JNC VIII criteria. The overall prevalence of hypertension in the present study (30.5%) was lower compared to study conducted in Raichur by Chethana et al 2,4,6 The prevalence was higher in comparison with the prevalence reported in study conducted by Bhardwaj et al in Nagpur as well as studies done by Mohan in Chennai and By Kaur et al in South India. [7][8][9] Female exhibit higher prevalence of hypertension than their male counterparts (F: 53.6% and M: 46.4%).…”
Section: Discussioncontrasting
confidence: 65%
“…While studies done in Varanasi by Singh et al and by Singh in Rewa showed prevalence is more in males than females. 4,10 Higher prevalence in females is found in study conducted by Reddy et al on Indian industrial population. 11 This may contribute to exposure of more female population while doing survey, as male members were out of house for working purpose during our visit hours.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Evidence from the literature identifies hypertension as a significant public health concern, given its increased prevalence across the world (Ahmed et al, 2014;Abebe et al, 2015;Lasisi, Abiona, & Gureje, 2010;Mendis, 2010). Singh, Shankar, and Singh (2017) noted that hypertension accounts for 7.5 million deaths globally, as a result of increased blood pressure. Common causes of death due to hypertension include heart disease, strokes, and frequent renal failure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of studies have been done in this global concern. A research done in the city Varanasi by Singh et al [5] as per census 2011, which is a community, based crosssectional study among 640 people aged between 25 to 64 years. According to Body Mass Index (BMI) values, study subjects either overweight or obese are more than one-third.…”
Section: Research Articlementioning
confidence: 99%